One day on our blue planet : in the Outback - Bailey, Ella (Bailey, Ella. One day on our blue planet., 2020)
"From Ella Bailey's acclaimed series of children's books comes another tale of how one young animal friend spends his day. He's only a little kangaroo in the middle of the vast Australian outback, but that doesn't stop him being curious and learning all about life in his corner of our blue planet." -- Amazon.